MANAJEMEN PENDIDIKAN KEWIRAUSAHAAN PESANTREN BERBASIS SYARI'AH STUDI KASUS DI PP. FATHUL ULUM JOMBANG: CASE STUDI IN PP. FATHUL ULUM JOMBANG - Fathur Rotib; Haris Supratno (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2022)
This study examines the model of sharia-based entrepreneurship education at the Fathul Ulum Puton Islamic Boarding School in Diwek Jombang. This research is a type of field research with a qualitative approach, namely research that does not carry out quantitative data calculations, with a naturalistic or predictive paradigm. Data were collected from a natural setting as a direct data source. The findings of this study are: 1) The entrepreneurial values that are realized in the Fathul Ulum Islamic Boarding School are the values of worship-based entrepreneurship, where all economic activities carried out are intended to worship Allah SWT; 2) The entrepreneurial education process carried out with the strategy of students being trained to manage economic institutions in Islamic boarding schools under the supervision and guidance of kiai and boarding school administrators.